Proceedings of the International symposium on fine arts in the east and the west (Japanese National Commission for UNESCO, 1966)
This booklet is intended to give an account of the international symposium on fine arts in the East and the West which was organized in Tokyo from 7 to 12 March 1966 by the Japanese National commission for Unesco, in collaboration with Unesco, the Japanese National committee of the international association of art and the Japanese section of the international association of art critics. It consists of two parts. Part I comprises the schedule, general information, and the report of the symposium which was adopted at the closing of the symposium, part II is the collection of papers, on the basis of which each expert made verbal lecture on one of the subjects previously set down.